RADON CONCENTRATION IN SOIL OF FALLUJAH, RAMADI, DIAYALA, WASIT AND NEARBY BAGHDAD SITES USING ssntds - Khadim, Nidhala; Ghayb, Dawser; Ahmed, Noor (Iraqi Journal of Science, 2024)
Solid state nuclear track detectors are increasingly being used to obtain the radon concentration in soil of some regions of Iraq. Several samples of soil were collected from Al – Anbar, Wasit, Diayala and Baghdad nearby sites to evaluate the radon concentration. CR – 39 plastic track detectors was used as a measurement device with cylindrical diffusion Technique. Results shows higher concentration was recorded in Al – Ramadi city which was equal to 143.1 Bq/m3, while the lower radon concentration was found in Diayala governorate which was equal to 21.504 Bq/m3. By making a comparison between results and the permissible limits of radon concentration in soil of ICRP, we found that all sites of the study are in agreement with the permissible limits.